Vibration and Exercise Maneuvers to Minimize Patients’ Shoulder Pain Post laparoscopic cholecystectomy: A Randomized Clinical Trial - Ali, Noorah Mahmoud; Kadhim, Alaa Jawad; Khachian, Alice (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): To determine the effect of the application of vibration and exercise on shoulder pain for patients after laparoscopic cholecystectomy.Methods: A Randomized Clinical Trial was carried out at Surgical Wards in AL-Kindi Teaching Hospital and Baghdad Teaching Hospital from November 13th to June 30th, 2023. After sample calculated from population, 70 patients were divided into two groups: the study group (35) and the control group (35) to achieve the objectives of the study. In the study group, a vibration device and shoulder exercises were used, both of which had validity and reliability, and pain was evaluated using numerical pain scale from (0-10). The researcher used a dice cube to investigate randomness, and the interview method was chosen for data collection.Results: The results of the data showed that all 70 patients had severe shoulder pain after laparoscopic cholecystectomy in the pre-test, while the results in the post-test of the application were decrease pain level by the application of both vibration and exercises.Conclusions: The study conclude that both vibration and exercises have a positive relationship in reducing shoulder pain, but the trail of vibration application on the shoulder has an effective effect on reducing the severity of shoulder pain compared to exercises.Recommendations: The study recommended that the vibration and exercise experience be applied to all patients after laparoscopic cholecystectomy